2010
DOI: 10.3389/fnene.2010.00131
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in Close Vicinity of Glioma Cells: Correlation Between Phenotype and Metabolic Alterations

Abstract: Microglia are immune cells within the central nervous system. In brain-developing tumors, gliomas are able to silence the defense and immune functions of microglia, a phenomenon which strongly contributes to tumor progression and treatment resistance. Being activated and highly motile, microglia infiltrate tumors and secrete macrophagic chemoattractant factors. Thereafter, the tumor cells shut down their immune properties and stimulate the microglia to release tumor growth-promoting factors. The result of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…A direct correlation has been shown between the immunogenicity of glioma tumor cells and the GAM content and their antigen-presenting function [78, 79]. In addition, the metabolic status of the microglia is altered by the glioma environment [80]. Abundant amounts of ATP released by the glioma have been suggested to trigger P2X 7 R signaling, resulting in increase of MIP-1 α (macrophage inflammatory protein-1 α ) and MCP-1 (monocyte chemoattractant protein-1) in GAMs [81].…”
Section: Interplay Between Gams and Gliomasmentioning
confidence: 99%
“…A direct correlation has been shown between the immunogenicity of glioma tumor cells and the GAM content and their antigen-presenting function [78, 79]. In addition, the metabolic status of the microglia is altered by the glioma environment [80]. Abundant amounts of ATP released by the glioma have been suggested to trigger P2X 7 R signaling, resulting in increase of MIP-1 α (macrophage inflammatory protein-1 α ) and MCP-1 (monocyte chemoattractant protein-1) in GAMs [81].…”
Section: Interplay Between Gams and Gliomasmentioning
confidence: 99%
“…The antitumor properties, namely glioma-cytotoxic effects of microglia, could only be shown in vitro so far [147, 148]. Favoring gliomas' growth could be due to a suppression and/or control of microglial cells by glioma cells and glioma-derived molecules (e.g., their loss of phagocytic function [149]. It was also suggested that, under the influence of glioma cells, microglia develop a different, noninflammatory phenotype suppressing their defense properties [139, 144, 150].…”
Section: Microglia and Gliomasmentioning
confidence: 99%
“…They did not support T cell proliferative responses, and they did not constitutively express significant levels of inflammatory or anti-inflammatory cytokines when tested ex vivo. Phagocytic function was detectable in these experiments, however, other studies on rat microglia indicated that continued presence of glioma cells may inhibit this process (Voisin et al, 2010).…”
Section: Microglia and Macrophage Function In The Contest Of Malignanmentioning
confidence: 40%